Étudier l’imaginaire du stage en Institut Médico-Éducatif : un outil pour mieux situer le rapport à l’abstraction des jeunes accueillis - Antoine Agraz (Recherches en Éducation)
The object of this article is to decipher the imagination of the young people welcomed in IME (Medical educational institute) from the point of view of their representations of the training in internship. We join here a double theorical anchoring (Bachelard and G. Durand) to analyse the symbolic dimension of the training in internship in the IME, in the alder of the interest carried in the latter by the welcomed young people. How of the training in internship symbolically invested by the young people of the IME? What are the dominant images? The imagination of the young people of the IME determines their representation of the internship, thus the way she behaves to it. We shall also see that the history of the ideas in the field of the intellectual handicap and the pedagogy gives meaning to the study of the nuances and the hidden dimensions bound to the imagination of the internship in IME, which is not without engedering heavy educational consequences in touch with the process « learn ».